THE INTERRELATIONSHIP BETWEEN ACHIEVEMENT-ORIENTED MOTIVATION AND PRE-COMPETITION ANXIETY IN ADOLESCENT WRESTLERS (International Educators Conference, 2025)
This study explores the interrelationship between achievement-oriented motivation and pre-competition anxiety among adolescent wrestlers. The research aims to determine how the desire for success influences emotional regulation, confidence, and psychological stability before competitions. Using psychological assessment methods and motivational profiling, the study identifies key factors that affect athletes’ mental readiness and stress management. The findings indicate that wrestlers with strong achievement motivation experience lower levels of anxiety and demonstrate higher adaptability in competitive situations. The results emphasize the importance of psychological preparation programs that integrate motivational and emotional training for young athletes.